Variability in CoP during running gait - Thelin,Tindra; Wittenmark,Alva (2025)
Gait analysis has through previous studies been proven to be indicative of health and useful in monitoring recovery following injuries affecting walking and running gait. There are many parameters to measure regarding gait depending on the desired outcome of the analysis. This project focuses on center of pressure (CoP) data collected during running using a force plate instrumented treadmill (HP Cosmos, Germany). The data was collected from one participant at two different visits. Each collection visit resulted in collection of data at two different times during the running, 8 km/h and 10 km/h at the first visit and 8 km/h and 10,5 km/h at the second visit, resulting in a total of four data sets. The data was processed using Matlab and scripts were written to normalize for foot contact location and movement relative to the force plate origin since the foot progressed over the plate's surface while in contact with the moving carpet. Left and right foot forces were identified and the running cycle was divided into three different phases, loading response (37,5% of contact time), midstance (37,5% of contact time) and preswing (25% of contact time). Mean and standard deviation of the position of the CoP was calculated within the full stance as well as the three phases. Variability in each phase was then estimated from each individual stride by calculating the mean of the standard deviation. While a quantifiable measurement of variability was obtained, further studies are needed to properly assess the relevance of the calculated variability. The data appeared to contain potential noise, the source and impact of which require further research to ascertain and potentially exclude.
Keywords: CoP; center of pressure; force plate; running gait; gait analysis